Cerium Doping Double Perovskite Scintillator for Sensitive X‐ray Detection and Imaging. Issue 35 (19th May 2021) - Wang, Zhilin; Xu, Xieming; Wang, Shuaihua; Xu, Hui; Xu, Weiwei; Zeng, Qingyou; Deng, Guoping; Jiang, Yongzheng; Wu, Shaofan
Abstract: Scintillators are widely used for nondestructive testing, nuclear medicine imaging, space exploration and security inspection. Recently, lead halide perovskite scintillation crystals have been brought into focus due to their effective atomic number, fast scintillation decay time, strong luminous efficiency, and tunable band gap. However, their application is limited by lead toxicity. Here we report that Ce‐doping can increase sensitivity in lead‐free double perovskite crystals (Cs2 NaTbCl6 ) for X‐ray detection and imaging. The introduction of Ce ions as sensitizer can be used to improve the radioluminescence of the crystals. The light output of Ce : Cs2 NaTbCl6 crystals is about 52153 ph/MeV, which is 25 % higher than that of un‐doped crystal. The X‐ray sensitivity is significantly enhanced. Based on our scintillation film X‐ray detector the detection limit is 30 nGy ⋅ s −1, which is about 1/183 of the typical medical imaging dose. Our scintillating film has excellent imaging ability with spatial resolution of up to 10 lp/mm. This research shows that Ce : Cs2 NaTbCl6 perovskite crystal scintillators are promising materials for X‐ray imaging application. Abstract : Cerium‐ion doped lead‐free double perovskite crystals (Cs2 NaTbCl6 ), were found to have significantly improved sensitivity and the double perovskite crystals (Ce : Cs2 NaTbCl6 ) showed excellent ability to resist X‐ray radiation damage. In addition the composite film of Ce : Cs2 NaTbCl6 crystals can reach a detection limit of 30 nGy ⋅ s −1 of X‐ray detector, with the capability to clearly distinguishing the spatial resolution of 10 lp/mm.